Respostas
respondido por:
1
a)h=x
catetos = raiz de 3 e raiz de 2
x^2=(raiz de 2)^2+(raiz de 3)^2
logo
x^2 = 2+3
x= raiz de 6
b)h=(3raiz de 5)^2
catetos= x e 6
h=raiz de (5.3^2)^2 = 45
45=36+x^2
x^2=45-36
x=raiz de 9
x = 3
catetos = raiz de 3 e raiz de 2
x^2=(raiz de 2)^2+(raiz de 3)^2
logo
x^2 = 2+3
x= raiz de 6
b)h=(3raiz de 5)^2
catetos= x e 6
h=raiz de (5.3^2)^2 = 45
45=36+x^2
x^2=45-36
x=raiz de 9
x = 3
respondido por:
0
Resposta:
a)h=x
catetos = raiz de 3 e raiz de 2
x^2=(raiz de 2)^2+(raiz de 3)^2
logo
x^2 = 2+3
x= raiz de 6
b)h=(3raiz de 5)^2
catetos= x e 6
h=raiz de (5.3^2)^2 = 45
45=36+x^2
x^2=45-36
x=raiz de 9
x = 3
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás